ANALISIS POLA SEBARAN DAN PERKEMBANGAN AREA UPWELLING DI BAGIAN SELATAN SELAT MAKASSAR - Inaku, Dwi Fajriyati (Torani Journal of Fisheries and Marine Science, 2017)
Waters of the southearn of Makassar Strait is a region which relatively rich of organic matter because the phenomenon of upwelling along the eastern season. The purpose of this research was to analyze the distribution patterns and the development of upwelling areas in the southern of Makassar Strait. This study used chlorophylla data and sea surface temperature from level 1 of Modis image for two years (2009 and 2010). The result showed that phenomenon of upwelling that occurs in the southern Makassar Strait appears since early June, the strongest upwelling in August and disapear in October. The upwelling was indicated by declining of sea surface temperature and increasing of chlorophyll-a concentration. Analysis of wind direction and speed indicate that the upwelling occurs in the southern Makassar strait spread to southwest with and estimated upwelling area around 46.000 km2. Keywords: upwelling, Makassar Strait, chlorophyll-a, sea surface temperature.